Preventing Religious Radicalism in Indonesian Society (Case of Gunungpati Subdistrict, Semarang City) - Masyhar, Ali; Pawenang, Eram Tunggul; Wahyudi, Wahyudi; Justicea, Nadela; Lagura, Syatriawan; Setiawati, Juniza Indah (Faculty of Law Universitas Negeri Semarang, 2022)
Acts of terror invariably commence with the cultivation of radicalism, making it imperative to implement preventive measures to curtail the proliferation of these extremist ideologies. Particularly noteworthy is the rise of social radicalism, which requires vigilant attention. The recent uptick in religious radicalism further underscores the urgency of fostering a preventive mindset. The objective of this initiative is to instill a preventive attitude among the residents of Gunungpati District in Semarang City, countering the influences of both terrorism and radicalism. Simultaneously, it seeks to offer valuable insights to the government, outlining necessary actions to provide legal protection for the people of Gunungpati District against religious sects associated with terrorism and radicalism. In collaboration with the Ats-Tsaqofah Semarang Foundation, an institution dedicated to community empowerment, particularly in the realm of religious morality development, this activity employs a combination of lecture, dialogue, and focused discussion methods. The utilization of the brainstorming method from the audience further enhances the initiative, extracting their initial knowledge about terrorism and radicalism. The anticipated outcome of this collaborative effort is the cultivation of preventive attitudes within society, acting as a counterforce against the infiltration of radical ideologies. By leveraging educational and community-based strategies, the initiative aims to equip individuals with the awareness and resilience needed to resist the allure of radicalism, thereby contributing to the overall security and well-being of the Gunungpati community.